THE EXPERIENCE OF DANCE AS A CONDITION FOR FOSTERING SOCIAL, TRADITIONAL AND CULTURAL SKILLS AMONG EARLY CHILDHOOD - Sari KATZ-ZICHRONY (Moldova State University, 2015)
An Early childhood dance program is a way to open the door to social competence, tradition learning and cultural integration besides achieving motor skills. The past few decades have demonstrated that dance education and the use of symbolic movement in early childhood, greatly enhance young children's learning. While a great amount of attention has been devoted to understanding how a variety of learning modes function in young children, an understanding of the benefits of dance education has not received strong recognition in the equation [3]. I suggest that movement and dance are the first communicative "language" that enables learning. Creating new contexts in and through dance for learning offers young children opportunities to understand and negotiate their community and the surrounding world. DANSUL CA CONDIŢIE ÎN FORMAREA COMPETENŢELOR SOCIALE, TRADIŢIONALE ŞI CULTURALE ÎN PERIOADA COPILĂRIEI TIMPURII Un program de dans specific copilăriei timpurii, pe lângă faptul că dezvoltă abilităţile motorii, este o modalitate de a forma competenţe sociale prin învăţarea tradiţiilor şi de integrare culturală. Ultimele decade au demonstrat că educaţia prin dans şi utilizarea mişcărilor simbolice în copilăria timpurie au un impact pozitiv asupra învăţării. În timp ce o mare parte de atenţie a fost acordată înţelegerii funcţionării variabilelor moduri de învăţare la copii, înţelegerea beneficiilor educaţiei prin dans nu s-a bucurat de aceeaşi recunoaştere din partea cercetătorilor. Sugerăm că mişcarea şi dansul sunt primele limbaje de comunicare care autorizează învăţarea. Crearea noilor contexte în şi prin dans oferă copiilor oportunităţi de a înţelege şi a negocia atât în cadrul comunităţii lor, cât şi în afara acesteia.